Perjudian Dalam Acara Malam Penghiburan di Jemaat sion Tiwoho Wilayah Wori I - Thomas, Art Semuel; Wagiu, Meily Meiny; Ompi, Meysi Regina Naomi (Jurnal Ilmiah Wahana Pendidikan, 2024)
The practice of gambling has been going on for a long time, and nowadays, with the development of science and technology, the practice of gambling is increasingly widespread, not only in urban areas but in all corners of the region, many people practice gambling. It is also undeniable that this is a serious problem that must be faced by the social sphere of society because gambling can cause things that can harm society, and it is the responsibility of the Church today when the practice of gambling is still rife even in a case that researchers observed. that worship activities become a means of legitimizing the practice of gambling, for example in consolation night services when someone dies, gambling becomes an entertainment while looking after the body and accompanying a family who is mourning, and this is difficult for the security forces to handle because of the nightly activities the consolation is still within the corridors of the Church which handles it, so that the Church itself indirectly becomes an instrument of legitimacy for the practice of gambling carried out at consolation night events.